Use of Polyglycolic Acid Sheets for the Prevention of Pancreatic Fistula after Laparoscopic Gastrectomy: A Single-Center Retrospective Study - Iwasaki, Kenichi; Barroga, Edward; Enomoto, Masaya; Matsumoto, Moe; Yamada, Erika; Miyoshi, Kenta; Shimoda, Yota; Ota, Yoshihiro; Nakagawa, Yuichi (The American surgeon, 2023)
Laparoscopic gastrectomy (LG) indications have been extended to advanced gastric cancer requiring expansive lymph node dissection. Despite the huge benefits of this minimally invasive surgery, major complications such as postoperative pancreatic fistula (POPF) remain a concern. With technical advances in surgical procedures, the treatment outcomes of gastric cancer surgery have improved. However, effective methods for preventing POPF have not yet been established. Herein, we examined the usefulness of polyglycolic acid (PGA) sheets for preventing POPF after LG. We retrospectively assessed 142 patients who underwent curative LG at our institution between January 2017 and August 2022. The 142 patients were divided into 2 groups; PGA group (n = 61): the site of lymph node dissection at the superior margin of the pancreas and pancreatic head was covered with PGA sheets, and nPGA group (n = 81): the site was not covered. We retrospectively compared the short-term surgical outcomes including POPF incidence. There was no significant difference in the background factors between the 2 groups and in the incidence of Grade II or higher postoperative complications according to the Clavien-Dindo (CD) classification. However, the incidence of CD Grade II or higher POPF was significantly lower in the PGA group than in the nPGA group (.0% vs 2.3%, respectively, = .007). There was no POPF in any of the 61 patients in the PGA group. This outcome suggests that POPF incidence may be reduced by covering the lymph node dissection site with PGA sheets after LG.